The efficacy and safety of rituximab in treating childhood nephrotic syndrome: an Italian perspective - Maratea, Dario (Ital J Pediatr, 2016)
BACKGROUND: Nephrotic syndrome is a disorder characterized by proteinuria, hypoalbuminemia and dyslipidemia. Low-dose alternate-day steroid regimen is the standard of care. In case of relapse or significant adverse events, steroid-sparing agents may be used. This analysis was aimed at assessing the efficacy and safety of rituximab for the treatment of children with nephrotic syndrome. RESULTS: Four studies were included in the final meta-analysis. The end-point of our analysis was the percentage of patients in remission at 6 months. Pooled data from the four studies favours the use of rituximab (RR 5.25, 95 % CI: 3.05–9.06; p < 0.0001). As regards the safety data, rituximab has a limited number of adverse effects, the most common of which occur during the infusions. CONCLUSIONS: In Italy, the off-label use of drugs is regulated by Law 648/96. In our opinion, there are three scientific requirements to merit a conditional national reimbursement for rituximab in nephrotic syndrome: 1. favourable clinical efficacy and safety data; 2. no available alternatives; 3. outcome data collecting by AIFA through prescribers. In conclusion, our results report a significant incremental benefit of adding rituximab to corticosteroid and/or calcineurin inhibitors for the treatment of nephrotic syndrome.